2014
DOI: 10.1073/pnas.1319221111
|View full text |Cite
|
Sign up to set email alerts
|

Yeast DJ-1 superfamily members are required for diauxic-shift reprogramming and cell survival in stationary phase

Abstract: The yeast Hsp31 minifamily proteins (Hsp31, Hsp32, Hsp33, Hsp34) belong to the highly conserved DJ-1 superfamily. The human DJ-1 protein is associated with cancer and neurodegenerative disorders, such as Parkinson disease. However, the precise function of human and yeast DJ-1 proteins is unclear. Here we show that the yeast DJ-1 homologs have a role in diauxic-shift (DS), characterized by metabolic reprogramming because of glucose limitation. We find that the Hsp31 genes are strongly induced in DS and in sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 39 publications
4
58
0
1
Order By: Relevance
“…4B). This increased expression in response to an ROS-inducing agent has been observed previously (22,26).…”
Section: Hsp31 Is An Integral Part Of the Yeast Cellular Stresssupporting
confidence: 85%
See 3 more Smart Citations
“…4B). This increased expression in response to an ROS-inducing agent has been observed previously (22,26).…”
Section: Hsp31 Is An Integral Part Of the Yeast Cellular Stresssupporting
confidence: 85%
“…In yeast, deletion of the ATG1 gene reduced the clearance of ␣Syn aggregates (66). Deletion of HSP31 was also demonstrated to impair autophagy under carbon starvation conditions (22). These studies raise the possibility that Hsp31 could be promoting autophagy of aggregated protein.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 93%
See 2 more Smart Citations
“…Therefore, this venerable model system presents some peculiar technical challenges to the study of DJ-1 superfamily proteins. The comprehensive study by MillerFleming et al, reported in PNAS, addresses these complications and finds that the S. cerevisiae Hsp31 minifamily plays a key role in the transition of proliferating yeast cells through diauxic shift then into a nonproliferative state known as stationary phase (5). The authors report that yeast Hsp31 family proteins are candidate upstream modulators of target of rapamycin complex 1 (TORC1), an important kinase that regulates nutrient sensing and cell proliferation and has been implicated in the function of human DJ-1 as well.…”
mentioning
confidence: 99%